Level 1 vulnerability criterion for the dead ship condition: A practical methodology for embedding operational limitations. (15th March 2023) - Bulian, Gabriele; Francescutto, Alberto
Abstract: The framework of second generation intact stability criteria (MSC.1/Circ.1627) allows introducing so-called "operational limitations", by specifying alternative environmental conditions based on the expected operation of the ship. Relevant calculation parameters of the criteria are correspondingly modified, according to standardized procedures specified by the Explanatory Notes. This is a significant novelty, and information is available for implementing operational limitations for most of the failure modes and levels of assessment. However, this is not the case for the level 1 vulnerability criterion for the dead ship condition. Therefore, the paper investigates the development of a rational simple procedure to contribute filling this gap. The devised approach provides a tool for determining a modified reference wind speed based on the environmental conditions representative of the considered operational limitations. Specifically, the modified wind speed is defined as the wind speed with a specified probability of exceedance. The reference probability of exceedance is determined considering the standard conditions and assumptions in the framework of MSC.1/Circ.1627. The modified reference wind speed can then be used to re-define all the calculation parameters of the criterion, according to the relevant theoretical background. Two example applications of the devised approach are also provided. Highlights: Operational limitations in the frame of second generation intact stability criteria. Focus on level 1 vulnerability assessment for dead ship condition (DS-L1). Development of a simple methodology for operational limitations in DS-L1. Two example applications: Mediterranean Sea and geographical areas worldwide. Procedure possibly relevant also for level 1 assessment for excessive acceleration.